2018
DOI: 10.18632/aging.101693
|View full text |Cite
|
Sign up to set email alerts
|

Association of gut microbiota composition and function with a senescence-accelerated mouse model of Alzheimer’s Disease using 16S rRNA gene and metagenomic sequencing analysis

Abstract: Although an intriguing potential association of the gut microbiome with Alzheimer's disease (AD) has attracted recent interest, few studies have directly assessed this relationship or underlying mechanism. Here, we compared the gut microbiota composition and functional differentiation of senescence-accelerated mouse prone 8 (SAMP8) mice with control senescence-accelerated mouse resistant 1 (SAMR1) mice using 16S rRNA gene and metagenomic sequencing analysis, respectively. Specifically, 16S sequencing results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 44 publications
4
52
0
Order By: Relevance
“…Multiple researches indicate that microbial colonization of the gut is linked to dementia pathogenesis via detrimental effects on metabolic disorders or low-grade inflammation progress, leading to damage to the brain [33] . Consistent with previous studies [34] , our findings provided further evidence that the microbiota-gut-brain axis may be involved in AD-like pathogenesis in SAMP8. PCoA and microbiota composition analysis revealed that the cluster from salidroside-treated SAMP8 was more similar to that of SAMR1, whereas the cluster from untreated SAMP8 was the most distinct.…”
Section: Discussionsupporting
confidence: 92%
“…Multiple researches indicate that microbial colonization of the gut is linked to dementia pathogenesis via detrimental effects on metabolic disorders or low-grade inflammation progress, leading to damage to the brain [33] . Consistent with previous studies [34] , our findings provided further evidence that the microbiota-gut-brain axis may be involved in AD-like pathogenesis in SAMP8. PCoA and microbiota composition analysis revealed that the cluster from salidroside-treated SAMP8 was more similar to that of SAMR1, whereas the cluster from untreated SAMP8 was the most distinct.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly to SCZ, the inflammatory patterns in BD are characterised by increased levels of TNF-α, the soluble TNF receptor type 1 (sTNF-R1) and the soluble IL-2 receptor (sIL-2R) compared with HC 48. Of note, there are intriguing findings, although still at the level of experimental preclinical data, suggesting that perturbations of the gut microbiota composition and the functional metagenome may be associated with accelerated ageing in animal models 49. In summary, the literature shows that: (1) there is a plausible interaction between inflammation and TS in modulating the risk of severe psychiatric disorders, and (2) this association might reflect (or be modulated) by specific detrimental alterations of the microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…cardiovascular diseases, tumors, Alzheimer's disease, CKD etc.) which may also in uence abundance and diversity of gut microbiota [7,[25][26][27][28]. The correlation between gut microbiota composition and lifestyle or speci c medications need to be further clari ed at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of this stable ecosystem, characterized by increased potential pathogens or decreased "bene cial" bacteria, probably implies imbalance induced by disease. Accumulating researches have suggested that potential function of gut microbiome is closely related to fatty acid metabolism, oxidative stress resistance, regulation of insulin sensitivity in diabetes, as well as arteriosclerosis and thrombosis in atherosclerotic diseases [5][6][7][8]. Moreover, approach using microbial markers for diseases identi cation has been proposed and proven feasible.…”
mentioning
confidence: 99%